TANGGUNG JAWAB NOTARIS DALAM MELEGALISASI SURAT JUAL BELI SECARA MELAWAN HUKUM TERHADAP JUAL BELI KIOS SEBAGAI HARTA BERSAMA YANG DILAKUKAN OLEH ISTRI TANPA PERSETUJUAN MANTAN SUAMI SETELAH TERJADINYA PERCERAIAN (STUDI PUTUSAN NOMOR: 598 K/PDT/2017) - Anitha Rosmauli Nainggolan; Budiman Ginting; Hasim Purba (Program Magister Ilmu Hukum Universitas Pancasila, 2021)
A notary as a general official who makes the deed is given the authority to legalize an underhand deed for every appearer who comes to him. Legalization carried out by a Notary basically must be carried out with the principle of prudence in order to avoid legal conflicts that have the potential to be present in the legalization of the deed. Examples of legal issues related to the legalization of private deeds can be seen in decision number 598 K/PDT/2017. The decision stated that the Notary had committed an unlawful act against the legalization of the sale and purchase agreement letter of the kiosk which was basically a joint property in which one of the parties was not involved in the sale and purchase agreement of the kiosk. Thenotary in the decision number 598 K/PDT/2017 can be observed that for his negligence in determining the objective conditions of the contents of the agreement, the judge was decided to commit an unlawful act by the judge on the basis of Article 1365 of the Civil Code. The precautionary principle is the standard of assessment in determining that a notary has committed an unlawful act in legalizing a sale and purchase agreement. The legal force of legalizing a letter of sale and purchase of a kiosk that is legally flawed is that the deed does not have perfect proving power. The parties who play a role in causing harm to the plaintiff for the sale and purchase must be categorized as parties who commit acts against the law for the sake of legal certainty as referred to in Article 1365 of the Civil Code